MOLECULAR DOCKING STUDIES OF ANTIDIABETIC ACTIVITY OF CINNAMON COMPOUNDS - Ganugapati, Jayasree; Swarna, Sruthi (Asian Journal of Pharmaceutical and Clinical Research, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE TE <![endif]--> ABSTRACT Objective: Diabetes mellitus is a prevailing problem in most of the countries. It occurs due to the lack of insulin or production of insufficient amount by pancreatic islets. Insulin is essential for maintaining blood glucose levels and hence is essential in the body. When inadequate amount of insulin is produced it has to be compensated by administration of insulin injections which is a painful procedure. To supplement the insulin needs, small molecules that can be administered through oral route and can mimic insulin action are considered in the present study. The objective of the present study is to perform In silico analysis of Cinnamon compounds to understand their insulin mimetic activity. Methods: Docking studies are essential to understand the interaction between the protein and the ligands. In our study we have selected the insulin receptor as the crucial protein and ligands from Cinnamon. QSAR, Toxicity and ADMET properties of these compounds are calculated using Osiris property calculator, Molinspiration, and preADMET calculator. Docking studies were performed using Autodock 4.0 and Argus Lab 4.0. Results: Based on these properties out of 10 compounds- we have selected 2 best compounds which had no side effects and were docked with insulin receptor .The energy values obtained for 3, 4, 5-trimethoxy cinnamic acid is -6.6 and for 2-chloro cinnamic acid is -8.3 kcal/mol. Autodock results indicate that these ligands interact with crucial residues in the active site region. Conclusion: From the Argus lab and Autodock studies, the best pose was obtained with least energy value from which it can be hypothesized that these 2 compounds can be considered as potential activators of insulin receptor. Further wet lab studies have to be performed to confirm the properties of these 2 compounds. Key Words: Cinnamon, Diabetes, Docking, Insulin mimetics ,Insulin receptor. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->